Being there without being there: Gifts compensate for lack of in‐person support. Issue 6 (31st January 2022) - Wiener, Hillary J. D.; Howe, Holly S.; Chartrand, Tanya L.
Abstract: Providing social support is a critical part of being in a relationship with someone, but people often struggle to support loved ones in person. In this paper, we show how givers can use gifts to compensate for not providing in‐person social support. Study 1 shows that when it is prohibitively difficult for givers to provide in‐person support, they give more expensive gifts. Study 2 replicates this effect for likelihood to give a gift and shows it is not due to social desirability. Studies 3, 4a, and 4b find that guilt over not having provided adequate support drives people to give gifts, and that giving gifts partially relieves givers' feelings of guilt. Studies 5 and 6 examine moderation. In Study 5, people only compensate for a lack of in‐person support with a gift when they have a strong obligation to support the recipient because they are close to them. Study 6 shows that money does not substitute for in‐person support. We show the role of gifts in enhancing givers' wellbeing and provide new customer insights to managers on reasons people purchase gifts.